2013
DOI: 10.3144/expresspolymlett.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the processability, morphology and biodegradability of clay incorporated PLA/LLDPE blends via selective localization of nanoclay induced by melt mixing sequence

Abstract: Abstract. Polylactic acid (PLA)/linear low density polyethylene (LLDPE) blend nanocomposites based on two different commercial-grade nanoclays, Cloisite ® 30B and Cloisite ® 15A, were produced via different melt mixing procedures in a counter-rotating twin screw extruder. The effects of mixing sequence and clay type on morphological and rheological behaviors as well as degradation properties of the blends were investigated. The X-ray diffraction (XRD) results showed that generally the level of exfoliation in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Similarly, Chen and coworkers [16,17] compared the influence of organoclay and twice functionalized clay on the morphology and properties of PLA/poly(butylene succinate) (PBS) and PLA/poly(butylene succinate-co-butylene adipate) (PBSA) blends. Recently, As'habi et al [18] studied the effect of mixing sequences and organoclay types on the morphological, rheological and degradation behavior of PLA/low density polyethylene (LLDPE) nanocomposites. The PLA/LLDPE/clay nanocomposites were prepared using two commercially available organically modified montmorillonite (OMMT): Cloisite ® 30B (C30B) and Cloisite ® 15A (C15A).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chen and coworkers [16,17] compared the influence of organoclay and twice functionalized clay on the morphology and properties of PLA/poly(butylene succinate) (PBS) and PLA/poly(butylene succinate-co-butylene adipate) (PBSA) blends. Recently, As'habi et al [18] studied the effect of mixing sequences and organoclay types on the morphological, rheological and degradation behavior of PLA/low density polyethylene (LLDPE) nanocomposites. The PLA/LLDPE/clay nanocomposites were prepared using two commercially available organically modified montmorillonite (OMMT): Cloisite ® 30B (C30B) and Cloisite ® 15A (C15A).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the addition of a compatibilizer to a nanofiller-containing multiphase system can contribute towards nanofiller positioning and its state of dispersion due to the induced changes in the thermodynamic system [98]. Mallick et al [99] reported the synergistic effect of nanoclay and maleic anhydride-grafted polyethylene (PE-g-MA) on the morphology and properties of nylon 6/high density polyethylene (HDPE) blends.…”
Section: Effects Of Polymeric Compatibilizer On Thementioning
confidence: 99%
“…A less expensive and more practical strategy to overcome these drawbacks is the blending of PLA with other polymers. Hence, several synthetic polymers and copolymers such as, polyethylene , polypropylene (PP) , polystyrene , poly(ethylene terephtalate) , polycarbonate , polyamide , and acrylonitrile‐butadiene‐styrene (ABS) or biodegradable polymers such as polycaprolactone , poly(butylene succinate) , poly(butylenes adipate‐co‐terephtalate) , thermoplastic starch , and poly(butylene succinate adipate) have been used.…”
Section: Introductionmentioning
confidence: 99%